La frontière syro-jordanienne dans le conflit syrien : enjeux sécuritaires, gestion frontalière - Cyril Roussel (L'Espace Politique)
Since the beginning of the Syrian conflict, the Kingdom of Jordan has to administrate a major crisis on the other side of its northern border. Even if Amman agreed to receive hundreds of thousands of refugees, the security issue still remains central about how this border is considered. We will analyse how Jordan, during this whole long-lasting conflict, chose to secure the northern part of its territory, as the jihadist threat is growing stronger in the South of Syria.